2011
DOI: 10.5304/jafscd.2011.021.021
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Food Environment: From Theory to Planning Practice

Abstract: The retail food environment is becoming an increasingly important consideration in land use planning decisions. Although many municipal official (or comprehensive) plans call for improved food environments, there are no standard methods by which to assess the implementation of policies reflecting these priorities. Methods developed to assess policy enforcement should be feasible to implement by urban planners and developers, should show some correlation between food environments and residents' health or diet o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…This issue is not confined to rural food environment research, but is reflective of the broader field, with Glanz et al [10] reporting 50.4% of their reviewed studies examining the reliability of tools, 30.4% testing for validity and only 13.6% investigating sensitivity to change. Other researchers have found similar results [18,25,28], however, no clear benchmarks are available, against which the reliability, validity and sensitivity of food environment tools can be assessed [14,26,66].…”
Section: Discussionmentioning
confidence: 58%
“…This issue is not confined to rural food environment research, but is reflective of the broader field, with Glanz et al [10] reporting 50.4% of their reviewed studies examining the reliability of tools, 30.4% testing for validity and only 13.6% investigating sensitivity to change. Other researchers have found similar results [18,25,28], however, no clear benchmarks are available, against which the reliability, validity and sensitivity of food environment tools can be assessed [14,26,66].…”
Section: Discussionmentioning
confidence: 58%
“…A large number of different measures seeking to capture the characteristics of neighborhood food environment have been employed in the existing literature. One common measure has referred to accessibility theories, which often reflect a geographical perspective of the food environment [ 23 , 24 ]. Approaches used to determine accessibility to different types of food outlets include the absolute number count or density [ 14 , 25 ], dominance of certain types of food outlets [ 13 ], path distance calculation [ 7 ], and geo-big data analysis [ 26 ].…”
Section: Previous Literaturementioning
confidence: 99%
“…food planning, which has recently emerged as a tool for improving the food environment and facilitating healthy eating. Although planners cannot control the food prices and what to sell in restaurants (Minaker et al, 2011), they can greatly contribute to restaurant environment improvement via zoning and licensing regulations. For example, Raja et al (2008) suggested that fast-food restaurants should be required to provide a "healthy offerings check", which certifies that healthy foods will be offered, from the local public health agency in the licensing process, when they are applying for a food establishment permit.…”
Section: From Community To Consumer Nutrition Environment: Policy and Planning Implicationsmentioning
confidence: 99%